Інтелектуальні технології у маркетинговому аналізі - Setlak, G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Procedures and algorithms for application of artificial intelligence in processing and analysing various types of knowledge are considered. It is proposed to integrate such techniques of knowledge and decision making modelling as neural networks and fuzzy logic-based reasoning methods. The problem of identification of complex processes is solved with the use of neuro-fuzzy systems. Examples of the proposed approach application in market analysis are given.